Waters of Belonging Al-miyahu Tajma'unah: Arabic Australians and the Georges River Parklands - Goodall, Heather (UTS ePRESS, 2012)
This book arises from Parklands, Culture and Communities, a project which looks at how cultural diversity shapes people's understandings and use of the Georges River and green spaces in Sydney's south west. Culturally diverse uses and views have not often been recognised in Australia in park and green space management models, which tend to be based on Anglo-Celtic 'norms' about nature and recreation. This book focusses on the experiences of four local communities - Aboriginal, Vietnamese, Arabic and Anglo Australians - and their relationships with the river, parks and each other.